When is rotational angiography superior to conventional single‐plane angiography for planning coronary angioplasty?. Issue 4 (27th May 2015) - Morris, Paul D.; Taylor, Jane; Boutong, Sara; Brett, Sarah; Louis, Amal; Heppenstall, James; Morton, Allison C.; Gunn, Julian P.
Abstract : Objectives: To investigate the value of rotational coronary angiography (RoCA) in the context of percutaneous coronary intervention (PCI) planning. Background: As a diagnostic tool, RoCA is associated with decreased patient irradiation and contrast use compared with conventional coronary angiography (CA) and provides superior appreciation of three‐dimensional anatomy. However, its value in PCI remains unknown. Methods: We studied stable coronary artery disease assessment and PCI planning by interventional cardiologists. Patients underwent either RoCA or conventional CA pre‐PCI for planning. These were compared with the referral CA (all conventional) in terms of quantitative lesion assessment and operator confidence. An independent panel reanalyzed all parameters. Results: Six operators performed 127 procedures (60 RoCA, 60 conventional CA, and 7 crossed‐over) and assessed 212 lesions. RoCA was associated with a reduction in the number of lesions judged to involve a bifurcation (23 vs. 30 lesions, P < 0.05) and a reduction in the assessment of vessel caliber (2.8 vs. 3.0 mm, P < 0.05). RoCA improved confidence assessing lesion length ( P = 0.01), percentage stenosis ( P = 0.02), tortuosity ( P < 0.04), and proximity to a bifurcation ( P = 0.03), particularly in left coronary artery cases. X‐ray dose, contrast agent volume, and procedure duration were not significantly different. Conclusions: Compared with conventional CA, RoCA augments quantitative lesion assessment, enhances confidence in the assessment of coronary artery disease and the precise details of the proposed procedure, but does not affect X‐ray dose, contrast agent volume, or procedure duration. © 2015 Wiley Periodicals, Inc.